Acquired enamel pellicle engineering for protection against dental erosion: in vivo evaluation of the protective effect of sugarcane-derived cystatin (CaneCPI-5), hemoglobin and statherin-derived peptide (StN15) - Carvalho, Thamyris de Souza (2023)
Current study examined, in vivo 1) acquired enamel pellicle (AEP) protein composition after treatment of tooth surface utilizing sugarcane-derived cystatin (CaneCPI-5), human hemoglobin (HB), statherin-derived peptide (StN15) or its combination (Comb) prior AEP formation and following intrinsic or extrinsic erosive attack; 2) preventive potential of these treatments versus intrinsic or extrinsic enamel erosive demineralization. Ten volunteers participated in a crossover and triple-blind protocol, composed of ten phases. In every phase, following prophylaxis, volunteers rinsed (1 min; 10 mL) with (1) deionized H2O, (2) 0.1 mg/mL CaneCPI-5, (3) 1 mg/mL HB, (4) 1.88 × 10-5M StN15 or solution containing Comb (5). Following AEP formation (2h), enamel biopsy was performed on tooth 21. In this area, an erosive attack was executed utilizing 1% citric acid pH 2.5 or with 0.01 M HCl pH 2 for 10s. Calcium ions released from enamel were analyzed by Arsenazo method. The remaining teeth endured identical erosive challenges. Further, electrode filter papers soaked in 3% citric acid was utilized to collect AEP. Specimens were assessed by quantitative label-free proteomics. In extrinsic erosion, treatment utilizing proteins/peptides, alone or in combination, boosted multiple proteins acid-resistant within AEP in contrast to control. The greatest boost occurred on PRPs (32-fold, StN15), profilin (15-fold, combination), alpha-amylase (9-fold; StN15), keratins (8-fold, CaneCPI-5 and HB), histatin-1 (7-fold, StN15), immunoglobulins (6.5-fold, StN15), lactotransferrin (4-fold, CaneCPI-5), cystatins, lysozyme, S-100-A9 protein and actins (3.5-fold, StN15), serum albumin (3.5-fold, CaneCPI-5 and HB) and hemoglobin (3-fold, StN15). However, solely after proteins/peptides treatment, alone or in combination, Annexin, calmodulin, keratin, tubulin and cystatins were detected. Groups two, three and four had expressively lower enamel Ca release in contrast to group one (Kruskal-Wallis / Dunn\'s, p < 0.05). Thus, treatments with CaneCPI-5, HB or StN15 notably increase proteins acid-resistant within AEP, preventing erosion. In intrinsic erosion, the treatments also boosted multiple proteins acid-resistant within AEP in contrast to control. Observing an increase for PKM pyruvate kinase (11-fold, CaneCPI-5), immunoglobulins and submaxillary gland androgen-regulated protein 3B (4-fold, StN15), and Hb and lysozyme-C (2-fold, StN15). Multiple proteins not usually described within AEP, but that bind calcium or other proteins were exclusively in groups treated within tested proteins/peptides, alone or in combination. The mean concentrations (SD, mM) of calcium released from enamel were 3.67 ± 1.48a, 3.11 ± 0.72a, 1.94 ± 0.57b, 2.37 ± 0.90a and 2.38 ± 0.45a for groups 1-5, respectively (ANOVA/Tukey, p<0.05). Thus, treatments utilizing CaneCPI-5, HB or StN15 notably increased proteins acid-resistant within AEP, but only HB was able to prevent intrinsic erosion. Concluding, all the proteins/peptide evaluated increased proteins acid-resistant within AEP, regardless type of erosive challenge, but only Hb protected enamel against intrinsic erosion.